Sister's choice - Richards, Emilie, 1948- (Mira, 2008)
Childless Kendra and husband Isaac accept an offer from Kendra's younger sister- single mom Jamie- to conceive and carry a child for them. But when a medical crisis threatens Jamie's health she learns that the most difficult choice in her life is yet to come